Етнографічна експедиція на Харківщину і Луганщину - Артюх, А.; Васянович, О.; Гаврилюк, Н.; Гудченко, З.; Сироткін, В. (Народна творчість та етнографія, 2007)
The article is a report about ethnographic expedition of the members of the Ukrainian Ethnological Centre of Maksym Rylsky Institute of Art Criticism, Folklore and Ethnography by the Ukrainian Academy of Sciences. The research workers made expedition to Kharkiv oblast and Luhansk oblast in September 2007. The aim of expedition was to collect the facts for studying of ethnocultural development, relations between ethnic groups and national identity of people who live in this area. Methods of interview, questionnaire survey were used and they relate to various aspects of national culture and way of life: folk dwelling, family and calendar customs, common law, mythology etc.